Mobile devices: older people’s learning experiences - Azuddin, Muna; Abd Malik, Sofianiza; Mahmud, Murni (Institute of Electrical and Electronics Engineers, 2022)
Mobile devices are important to support older people in many ways, especially to promote independent ageing. However, rapid development of mobile devices which focus on younger people has incurred issues among older people to learn using it. Thus, this study aims to understand mobile device learning experiences among older people. Qualitative method was used in the study - interviews and focus groups, to collect data among 21 older people, aged 55 and above. It is found that older people initially experienced three stages of learning process: beginner, intermediate and advance. There are several learning techniques or resources required by older people to learn to use mobile devices. These resources are very critical for older people to maintain their positive emotions and attitudes. This study enhanced knowledge in user experience domain which can assist mobile designer to develop useful and usable mobile devices or technologies for older people and others.